Breeding performance of the Blue Tit Parus caeruleus in a patchy Mediterranean landscape - Catalan, R M; Haeger, J F (REVUE D ECOLOGIE-LA TERRE ET LA VIE, 1999)
This study compares reproductive strategy and breeding success of Parus caeruleus in a helm-oak (Quercus rotundifolia) forest and a pine plantation (Pinus pinea and P. pinaster) in the southern Iberian Peninsula. During the breeding period, an asymmetric flow of individuals takes place from the helm-oak forest to the pine plantation. This flow is favoured by nestboxes where Blue tits can lay their eggs. During the winter, a large part of the population moves back from the pine plantation to the helm-oak forest. Breeding pair density was much higher in the helm-oak forest than in the pine plantation. This may bt accounted for by the poorer quality of the resources available in the pine plantation which birds try to compensate for with larger breeding territories. Breeding density and most life-history traits examined (timing of breeding, clutch site, egg size, number of fledglings and fledgling weight) were similar in both habitats, as a result of the phenotypic plasticity of this species. Although breeding success was similar in both habitats, recruitment of new individuals per unit area was higher in the helm-oak forest. The consequences of pine plantations, as a form of forestry management, on species conservation is discussed.
APS
Keywords: breeding success; Holm oak; iberian peninsula; Parus caeruleus; Pinus pinaster; Pinus pinea; Quercus ilex; reproductive strategies